Ocena prehranjenosti bolnikov v Splošni bolnišnici Celje pred velikim operativnim posegom v trebušni votlini - Novak, Ernest (Zdravniški vestnik, 2001)
Background. Malnutrition has serious implications for recovery after surgery. Early detection of malnutrition with nutritional support minimizes postoperative complications. Nutritional assessment tools need to be simple and suitable for use in everyday practice. In our study we wanted to determine, how many patients might benefit from nutritional support. Methods. From April to August 1999 fifty consecutively admitted patients predicted to major abdominal surgery have been examined. We used Mini nutritional assessment (MNA), Buzbys nutrition risk index (NRI), blood albumin level and weight loss in the last 3 months period prior to the examination, to assess nutritional status. Results. We examined 50 patients (27 males and 23 females,age 76.5 +- 16.5) and confirmed malnutrition in 40% of patients with MNA and serum albumin level. The increased risk for nutrition-associated complications was confirmed by NRI and weight loss in 44%. Conclusions. A confident diagnosis of malnutrition and increased risk for nutrition-associated complications can be established by using a combination of simple methods like MNA, NRI, weight loss and serum albumin level. Almost half of the patients admitted for major abdominal surgery in General hospital Celje suffer from malnutrition and they may benefit with early nutritional intervention.
Keywords: Abdomen; bolniki; food; Izguba teže; Nutrition assessment; Nutrition disorders; operacije; podhranjenost; Predoperativna nega; prehrana; Prehrana, motnje; Prehrana, ocena; Preoperative care; Serum albumin; Serumski albumin; Surgery; trebušna votlina; Weight loss